The Effect of Two Infectious Diseases and Harvesting in the Eco-Epidemiological Model - Yaseen, Rasha Majeed (Al-Nahrain Journal of Science, 2018)
In this paper, an Eco-Epidemiological model with different infectious diseases in prey population and the optimal harvesting in predator population is proposed and studied. Linear type used to describe the functional response. Sufficient and necessary conditions for existence each equilibrium points of the system are established, the bounded and stability analysis of all possible equilibrium points are studied. The effect of harvest on the stability of this system is investigated. Finally, the dynamical behavior of system is discussed using Numerical simulation.